2017
DOI: 10.1093/gbe/evx002
|View full text |Cite
|
Sign up to set email alerts
|

Amoebozoans are Secretly but Ancestrally Sexual: Evidence for Sex Genes and Potential Novel Crossover Pathways in Diverse Groups of Amoebae

Abstract: Sex is beneficial in eukaryotes as it can increase genetic diversity, reshuffle their genomes, and purge deleterious mutations. Yet, its evolution remains a mystery. The eukaryotic clade supergroup Amoebozoa encompasses diverse lineages of polymorphic amoeboid forms, including both free-living and parasitic lineages. The group is generally believed to be asexual, though recent studies show that some of its members are implicated in cryptic forms of sexual cycles. In this study, we conduct a comprehensive inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 83 publications
(77 reference statements)
6
70
0
Order By: Relevance
“…Furthermore, this sexual behavior is supported with genetic evidence that reported nearly complete recombination gene repertoire in some members of this genus (Tekle et al. ; Wood et al. ).…”
supporting
confidence: 61%
“…Furthermore, this sexual behavior is supported with genetic evidence that reported nearly complete recombination gene repertoire in some members of this genus (Tekle et al. ; Wood et al. ).…”
supporting
confidence: 61%
“…The use of an integrative taxonomic approach can provide a better understanding of species distributions including taking into account cryptic species, phenotypic plasticity, population‐level variation, etc . Recent studies have shown that the use of single cell “omics” allows acquisition of data from the dark area particularly for uncultivable species . Hence, combining community and single cell approaches will help to increase our knowledge of this highly diverse clade.…”
Section: Discussionmentioning
confidence: 99%
“…Amoebozoan species include a variety of lineages of polymorphic amoeboid forms that until recently were considered to be asexual. A recent study, however revealed that amoebozoans representing all major subclades possess most of the genes that function specifically in meiosis, as well as many of the genes involved in meiotic recombinational repair [61]. It was concluded that Amoebozoa is ancestrally sexual.…”
Section: Amoebozoamentioning
confidence: 99%